Mobile Moodle to Support Graduate Students Self-Regulated Learning: An Ex-Post Facto Study - Atmoko, Septian Hanung Dwi; Kuswandono, Paulus (International Journal of Education, 2021)
The use of a mobile learning management system (LMS) has engendered pros and cons concerning the effects on influencing the students’ self-regulated learning (SRL). A large number of research studies concerning mobile-LMS have been done in the past decades. Studies have also demonstrated that the use of mobile LMS can facilitate the users as it can be conveniently accessed anywhere with their mobile phones. However, those studies have not comprehensively discussed the results of the students' mobile-LMS on their self-regulated learning development. Hence, this research aims to investigate the use of mobile learning management systems, specifically mobile Moodle, to support the students' self-regulated learning. An ex-post-facto research study was used to gather the respondents' data after they experienced the mobile Moodle and the relationship to the SRL development. The respondents were 15 students from English Education Master Program, Yogyakarta, Indonesia. Further, the questionnaires and interviews were used to gather and analyze the data. The results showed that most of the graduate students were facilitated by the use of mobile Moodle to develop their self-regulated learning. The result showed that the features, namely, upcoming events, messages, and chats, positively related to the students’ SRL construction. However, the participants highlighted the easiness of using reminder and notification features since some of the students cannot receive the notification directly to their phones. Thus, the mobile Moodle developer should improve it to maximize its benefit in influencing students’ SRL.